Mineral-leaching chemical transport with runoff and sediment from severely eroded rare-earth tailings in southern China - H. Lu; H. Lu; L. Cao; Y. Liang; J. Yuan; J. Yuan; Y. Zhu; Y. Zhu; Y. Wang; Y. Wang; Y. Gu; Y. Gu; et al. (Solid Earth, 2017)
Rare-earth mining has led to severe soil erosion in southern China. Furthermore, the presence of the mineral-leaching chemical ammonium sulfate in runoff and sediment poses a serious environmental threat to downstream water bodies. In this paper, the characteristics of mineral-leaching chemicals in surface soil samples collected in the field were studied. In addition, NH4+ and SO42− transport via soil erosion was monitored using runoff and sediment samples collected during natural rainfall processes. The results demonstrated that the NH4+ contents in the surface sediment deposits increased from the top of the heap (6.56 mg kg−1) to the gully (8.23 mg kg−1) and outside the tailing heap (13.03 mg kg−1). The contents of SO42− in the different locations of the tailing heaps ranged from 27.71 to 40.33 mg kg−1. During typical rainfall events, the absorbed NH4+ concentrations (2.05, 1.26 mg L−1) in runoff were significantly higher than the dissolved concentrations (0.93, 1.04 mg L−1), while the absorbed SO42− concentrations (2.87, 1.92 mg L−1) were significantly lower than the dissolved concentrations (6.55, 7.51 mg L−1). The dissolved NH4+ and SO42− concentrations in runoff displayed an exponentially decreasing tendency with increasing transport distance (Y = 1. 02 ⋅ exp( − 0. 00312X); Y = 3. 34 ⋅ exp( − 0. 0185X)). No clear trend with increasing distance was observed for the absorbed NH4+ and SO42− contents in transported sediment. The NH4+ and SO42− contents had positive correlations with the silt and clay ratio in transported sediment but negative correlations with the sand ratio. These results provide a better understanding of the transport processes and can be used to develop equations to predict the transport of mineral-leaching chemicals in rare-earth tailings, which can provide a scientific foundation for erosion control and soil management in rare-earth tailing regions in southern China.